A high-density genetic map for anchoring genome sequences and identifying QTLs associated with dwarf vine in pumpkin (Cucurbita maxima Duch.). (December 2015) - Zhang, Guoyu; Ren, Yi; Sun, Honghe; Guo, Shaogui; Zhang, Fan; Zhang, Jie; Zhang, Haiying; Jia, Zhangcai; Fei, Zhangjun; Xu, Yong; Li, Haizhen
Abstract Background Pumpkin (Cucurbita maxima Duch.) is an economically important crop belonging to the Cucurbitaceae family. However, very few genomic and genetic resources are available for this species. As part of our ongoing efforts to sequence the pumpkin genome, high-density genetic map is essential for anchoring and orienting the assembled scaffolds. In addition, a saturated genetic map can facilitate quantitative trait locus (QTL) mapping. Results A set of 186 F2 plants derived from the cross of pumpkin inbred lines Rimu and SQ026 were genotyped using the genotyping-by-sequencing approach. Using the SNPs we identified, a high-density genetic map containing 458 bin-markers was constructed, spanning a total genetic distance of 2, 566.8 cM across the 20 linkage groups ofC. maxima with a mean marker density of 5.60 cM. Using this map we were able to anchor 58 assembled scaffolds that covered about 194.5 Mb (71.7 %) of the 271.4 Mb assembled pumpkin genome, of which 44 (183.0 Mb; 67.4 %) were oriented. Furthermore, the high-density genetic map was used to identify genomic regions highly associated with an important agronomic trait, dwarf vine. Three QTLs on linkage groups (LGs) 1, 3 and 4, respectively, were recovered. One QTL, qCmB2, which was located in an interval of 0.42 Mb on LG 3, explained 21.4 % phenotypic variations. WithinqCmB2, one gene, Cma_004516, encoding the gibberellin (GA) 20-oxidase in the GA biosynthesis pathway, had a 1249-bp deletion in its promoter in bush type lines, and its expression level was significantly increased during the vine growth and higher in vine type lines than bush type lines, supportingCma_004516 as a possible candidate gene controlling vine growth in pumpkin. Conclusions A high-density pumpkin genetic map was constructed, which was used to successfully anchor and orient the assembled genome scaffolds, and to identify QTLs highly associated with pumpkin vine length. The map provided a valuable resource for gene cloning and marker assisted breeding in pumpkin and other related species. The identified vine length QTLs would help to dissect the underlying molecular basis regulating pumpkin vine growth.